Determinants of the half-turn with the ball in sub-elite youth soccer players - Zago, M.; Codari, M.; Grilli, M.; Bellistri, G.; Lovecchio, N.; Sforza, C. (Sports Biomechanics, 2016)
We explored the biomechanics of the 180° change-of-direction with the ball (half-turn) in soccer. We aimed at identifying movement strategies which enhance the players' half-turning performance, by characterising technique kinematics and understanding the structure of biomechanical and anthropometrics variables. Ten Under-13 sub-elite male players were recorded with an optoelectronic motion analyser while performing a 5-m straight dribbling followed by a half-turn with the sole. Joints kinematics differences between faster and slower trials were found in support-side hip rotation, driving-side hip adduction, trunk flexion and rotation, and arms abduction. To unveil the data-set structure, a principal component (PC) analysis and a stepwise linear discriminant analysis were performed using 30 biomechanical parameters and four anthropometric variables for each trial. Seven retained PCs explained 79% of the overall variability, featuring combinations of original variables that help in understanding the factors facilitating fast half-turns: keeping short steps, minimising lateral and forward body movements, and centre-of-mass lowering, even with ample lower limbs ranges of motion (RoM); abducting the upper limbs while limiting trunk flexion and pelvic inclination RoM. Balance and task-constrained exercises may be proposed to improve this technique. Moreover, a quantitative knowledge of the movement structure could give coaches objective insights to better instruct young players.